(untitled) (Scientific journal of the Fergana State University, 2026)
In the article, the role of farmers and peasants in creating the necessary conditions for the sustainable development of the livestock sector in the Republic, developing scientific research and international cooperation based on new innovative technologies, developing rural areas and improving the well-being of the population, as well as ensuring food security and employment of the population in rural areas. the issues related to playing an important role are highlighted.